Pengaruh Implementasi XBRL, Ukuran Perusahaan, dan Kepemilikan Manajerial Terhadap Kualitas Laporan Keuangan - Zikratul Ramadhan; Tri Utami Lestari (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to determine the simultaneous or partial effect of XBRL implementation, company size, and managerial ownership on financial reporting quality using the modified jones model in property and real estate companies listed on the Indonesia Stock Exchange in 2019-2021. This study uses quantitative methods. The unit of analysis used is a group, namely property and real estate companies listed on the Indonesia Stock Exchange in 2019-2021, and are the population in this study. By using the purposive sampling method, 66 companies were selected as research samples. The data analysis method used in this study is descriptive statistics and panel data regression analysis using Eviews 12 software. The results of this study indicate that XBRL implementation, company size, and managerial ownership simultaneously have a significant effect on financial reporting quality. Partially, company size has a significant positive effect on financial reporting quality, while XBRL implementation and managerial ownership have no significant effect on financial reporting quality.